2007
DOI: 10.1007/s10522-007-9107-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference as regards myocardial protein oxidation in aged rats: male rats have increased oxidative protein damage

Abstract: These data support the hypothesis that elevated levels of PCO, AOPP, and NT contribute to the extent of protein, but not lipid, oxidation in aged male rats. We are of the conviction that the increased myocardial Np-SH, GSH and RI levels that we have determined in aged male rats may be a protective factor in propagation of protein oxidation. Our findings support our conviction that protein and lipid oxidation, in the myocardial tissue of aged rats, have a controlling role in differing regulating mechanisms thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In animal studies, ROS generated in response to angiotensin II (AngII) are lower in female versus male mice. 23 Karali et al 24 suggest that there may be differing regulating mechanisms through gender differences; they have found that other oxidative stress parameters such as advanced oxidation protein products, nonprotein thiol, Fe 2+ , levels and the redox index were signifi cantly higher in male rats compared with female rats. These fi ndings support our hypothesis that an increase in production of ROS may be a contributing factor for higher TOS in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal studies, ROS generated in response to angiotensin II (AngII) are lower in female versus male mice. 23 Karali et al 24 suggest that there may be differing regulating mechanisms through gender differences; they have found that other oxidative stress parameters such as advanced oxidation protein products, nonprotein thiol, Fe 2+ , levels and the redox index were signifi cantly higher in male rats compared with female rats. These fi ndings support our hypothesis that an increase in production of ROS may be a contributing factor for higher TOS in men.…”
Section: Discussionmentioning
confidence: 99%
“…There is a causal relationship according to gender between different tumors and type 2 diabetes/metabolic syndrome as well. 24 Supposed pathomechanisms are obesity, cytokines secreted excessively in adipose tissue, permanent and postprandial and various diseases. 10,11 There is evidence that increases in oxidative stress contributes to complex functional and structural changes that ocur in the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Fe reacts avidly with ubiquitous, weak ROS such as superoxide anion and hydrogen peroxide to generate highly toxic hydroxyl radicals via Fenton/Haber-Weiss chemistry [26]. The main theoretical mechanism of protein carbonyl formation states that redox cycling cations such as Fe can bind to cation-binding locations on proteins and with the aid of further attack by hydrogen peroxide or superoxide anion can transform side-chain amine groups on several amino acids into carbonyls [26][27][28][29][30]. We showed that the concentrations of Fe in the serum and tissue were higher in acute pancreatitis groups compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The first example comes from the cardiovascular studies. Elevated levels of redox indexes (i.e., myocardial protein carbonyl and other protein oxidation parameters such as advanced oxidation protein products, nitrotyrosine, protein hydroperoxide, total thiols, non-protein thiols, 4-hydroxyalkenal, malondialdehyde, GSH and glutathione disulfide (GSSG)) have been hypothesized to contribute to the extent of protein, but not lipid, oxidation in aged male rats much more than in female (Kayali et al, 2007). The second paradigmatic example concerns metals.…”
Section: Cytology and Cytopathology In Male And Female Cells 721 Omentioning
confidence: 99%